The vital capital and its correlation with the GPD of the Republic of Belarus - Ramanouski, Artsiom V.; Maiseyeu, Maksim S. (Journal of the Belarusian State University. Economics, 2018)
Nowadays production of goods continues to be important but the production efficiency depends on the production technology, software, staff development, management system that is to say that the production efficiency depends on the effective use of human capital. Theodore Schultz (laureate of the Nobel Prize in economics) said: «All human resources and abilities are either inborn or acquired. Everyone is born with a set of individual genes, which defines its congenital human potential. Acquired valuable human qualities which can be improved by investments, we call human capital. » Human capital divided into three main parts: the vital (biophysical) capital, social capital, intellectual capital. The aim of the article is to look on the biophysical capital as one of variables which can have influence on GDP. The object of article is biophysical capital of the Republic of Belarus and its indicators: life expectancy at birth and total population. The subject of article is interdependence between vital (biophysical) capital and GDP. This article contains the GDP, life expectancyat birth and total population for the Republic of Belarus for the last 25 years (1990–2015). Moreover, this article contains correlation coefficients between following variables couples: GDP and life expectancy at birth; GDP and total population for the next countries: Republic of Belarus, Russian Federation, People’s Republic of China and others.
Keywords: human capital; human potential; vital (biophysical) capital; social capital; intellectual capital; life expectancy at birth; the Republic of Belarus; GDP; correlation coefficient